Inventory and Alternative Concept of Municipal Development for Area-Efficient Control of Settlement Development. The Example of the Halle-Leipzig Region - Sell, Thorben; Braunschweig, Björn; Bergfeld, Annedore; Henn, Sebastian (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
The development of residential areas in the context of settlement development is a significant driver regarding land use and thus critical in achieving the goal of reduced new land use to less than 30 hectares per day by 2030. Although spatial planning and spatial science have been addressing this issue for years, e.g. through consistent land management, the current land use in Germany amounts to around 52 hectares per day (as of 2019). This is i.a. because the control of settlement development often only intervenes in developments that go beyond the own communal development. Approaches to controlling self-development usually remain on a blanket level and thus promote decentralized decisions that, in total, contradict the set goals. The aim of this paper is to present a model for calculating self-development, which not only takes demographic development into account, but also aligns the size of self-development with site-specific requirements to consider the principles of spatial planning and thus promote sustainable spatial development. In its empirical basis, the paper is based on statistical analyses of the respective needs as well as surveys, interviews research results that have been carried out or have arisen within the framework of the BMBFfunded project Interko2.
Keywords: Self-development; Land use; Settlement development; Housing development; Spatial development